Structural Behavior of Concrete Produced Using Palm Kernel Shell (PKS) as a Partial Substitute for Coarse Aggregate (American Journal of Innovation in Science and Engineering, 2023)
The possibility that our available resources will soon run out completely cannot be overstated. There have been series of research into alternative materials, especially materials available locally which may be useful as a substitute alternative materials used in the production of concrete. This has become necessary due to increasing costs of construction and the need of reducing stresses in the environment in order to make construction more sustainable. The goal of this research was to assess the strength of concrete made with palm kernel shell (PKS) used in place of some of the coarse material. The experiments listed below were carried out: compressive strength test, slump test, sieve analysis, and water absorption test. The concrete was created using cement, sand, coarse stones (coarse materials), and palm kernel shell. For the compressive strength test, a total of 48 cubes with dimensions of 150 mm x 150 mm x 150 mm were cast, with the ratio of these materials being 1:1.5:3 (Cement: Sand: Aggregates), by weight batch. In place of the coarse aggregate, PKS of 0%, 10%, 20%, and 30% were used. Before the compressive strength was calculated, all of the samples were cured for 7, 14, 21, and 28 days. This experiment provides insight into how much concrete’s weight could be reduced while maintaining its strength. The outcomes of these tests were compared with the control group after completion. The findings showed that adding 10% palm kernel shell(PKS) to the concrete with coarse aggregate is beneficial without significantly reducing the concrete’s strength.